WALANT: A Discussion of Indications, Impact, and Educational Requirements - Shahid, Shahab; Saghir, Noman; Saghir, Reyan; Young-Sing, Quillan; Miranda, Benjamin H. (Archives of Plastic Surgery, 2022)
Wide-awake, local anesthesia, no tourniquet (WALANT) is a technique that removes the requirement for operations to be performed with a tourniquet, general/regional anesthesia, sedation or an anesthetist. We reviewed the WALANT literature with respect to the diverse indications and impact of WALANT to discuss the importance of future surgical curriculum integration. With appropriate patient selection, WALANT may be used effectively in upper and lower limb surgery; it is also a useful option for patients who are unsuitable for general/regional anesthesia. There is a growing body of evidence supporting the use of WALANT in more complex operations in both upper and lower limb surgery. WALANT is a safe, effective, and simple technique associated with equivalent or superior patient pain scores among other numerous clinical and cost benefits. Cost benefits derive from reduced requirements for theater/anesthetic personnel, space, equipment, time, and inpatient stay. The lack of a requirement for general anesthesia reduces aerosol generating procedures, for example, intubation/high-flow oxygen, hence patients and staff also benefit from the reduced potential for infection transmission. WALANT provides a relatively, but not entirely, bloodless surgical field. Training requirements include the surgical indications, volume calculations, infiltration technique, appropriate perioperative patient/team member communication, and specifics of each operation that need to be considered, for example, checking of active tendon glide versus venting of flexor tendon pulleys. WALANT offers significant clinical, economic, and operative safety advantages when compared with general/regional anesthesia. Key challenges include careful patient selection and the comprehensive training of future surgeons to perform the technique safely.
Keywords: WALANT; wide awake hand surgery; local anesthesia no tourniquet; education; training; simulation